2019
DOI: 10.13170/aijst.8.1.13060
|View full text |Cite
|
Sign up to set email alerts
|

A study of urban heat island of Banda Aceh City, Indonesia based on land use/cover changes and land surface temperature

Abstract: This article described the spatial and temporal of land surface temperature (LST) patterns in Banda Aceh City, Indonesia, in the context of urban heat island (UHI) phenomenon. Landsat imaginary in 1998 and 2018 was used in this study, which represents the conditions before and after the tsunami. Geographic Information System (GIS) and Remote Sensing (RS) technique were used for data analysis. The 1998 and 2018 LUC maps were derived from remote sensing satellite images using a supervised classification method (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…A similar figure was also reconstructed for the rest of the regions. The stable LST in Aceh contrasts with a study in Banda Aceh which found that the region has the potential for an increase in temperature [12]. Other studies also illustrate the fact that there is an increase in temperature in the Aceh region due to land-use changes [13].…”
Section: Resultsmentioning
confidence: 73%
“…A similar figure was also reconstructed for the rest of the regions. The stable LST in Aceh contrasts with a study in Banda Aceh which found that the region has the potential for an increase in temperature [12]. Other studies also illustrate the fact that there is an increase in temperature in the Aceh region due to land-use changes [13].…”
Section: Resultsmentioning
confidence: 73%
“…UHI is the phenomena where the temperature of an urban area is significantly higher than surrounding rural areas; it is one of the most significant challenges for the urban environment, especially in the context of global climate change [7]. Many remote sensing techniques using satellite images could detect the rapid alterations in the land use and land cover through several studies, which confirmed the surface UHI [10,11]. Naturally, the physical surface at urban environment consists of different built materials such as asphalt, gravel, stones, pebbles, concrete, etc., which characterizes with high heat capacities to store the solar energy.…”
Section: Introductionmentioning
confidence: 81%
“…Suriana et al (2020) found that UHI tends on built-up land and lower temperatures near water bodies, this information was only obtained from Landsat imagery. A similar method was applied in Banda Aceh, researchers found that UHI was positively and significantly correlated with building density (Achmad et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%